Korelasi Antara Penerapan Akad Mudharabah dan Profitabilitas Pada Bank Syariah Mandiri - Nuraini Nuraini; Azhar Muttaqin (Falah: Jurnal Ekonomi Syariah, 2018)
This research aims to know the correlation between implementation of mudharabah and the profitability in the Bank Syari’ah Mandiri. Quantitative approach was used in this research with Bank Syari’ah Mandiri as the subject. The research based on mudharabah development in Bank Syariah Mandiri, and it was observed from the data of financial statements that have been published in 2012 to 2016. The method is collecting data from Bank Syariah Mandiri financial statements in 2012 to 2016 and observing the data. Independent variable in this research is mudharabah and its dependent variable is profitability. The statistical method of data analysis used is a simple regression. The result showed that mudharabah as independent variable has correlation with profitability as dependent variable. It could be seen from the significant value which is 0,023 <0,05. Based on the significant value of the coefficient table can be said that mudharabah has a correlation with profitability positively and significantly, which is 0.023 <0.05.